Zinc Oxide Nanoparticles: chemical, physical and Biosynthesis Synthesis and its some Applications - Algarni, Rahma; Almalwi, Salwa (Journal of natural sciences, life and applied sciences, 2017)
This review article described the major synthesis of Zinc oxide nanoparticles with various ways, such as physical synthesis, chemical synthesis and Biosynthesis. Chemical synthesis as Hydrothermal Technique, Vapor Transport, Precipitation Method, Self-Combustion technique, Sol-gel method and microemulsion method.  Physical synthesis as high-energy ball milling method, laser ablation method and Physical vapor deposition method. Biosynthesis Includes synthesis through fungi, plants, bacteria Some applications of zinc oxide nanoparticles have been listed.
Keywords: Zinc oxide; Biosynthesis; metal oxide; nanoparticles